Loss of fine structure and edge sharpness in fast-spin-echo carotid wall imaging: measurements and comparison with multiple-spin-echo in normal and atherosclerotic subjects. - Biasiolli, L; Lindsay, A; Choudhury, R; Robson, M (2011)
PURPOSE: To test whether the k-space acquisition strategy used by fast-spin-echo (FSE) is a major source of blurring in carotid wall and plaque imaging, and investigate an alternative acquisition approach. MATERIALS AND METHODS: The effect of echo train length (ETL) and T(2) on the amount of blurring was studied in FSE simulations of vessel images. Edge sharpness was measured in black-blood T(1) W and proton density-weighted (PDW) carotid images acquired from 5 normal volunteers and 19 asymptomatic patients using both FSE and multiple-spin-echo (Multi-SE) sequences at 3 Tesla (T). Plaque images were classified and divided in group α (tissues' average T(2) ∼ 40-70 ms) and group β (plaque components with shorter T(2) ). RESULTS: Simulations predicted 26.9% reduction of vessel edge sharpness from Multi-SE to FSE images (ETL = 9, T(2) = 60 ms). This agreed with in vivo measurements in normal volunteers (27.4%) and in patient group α (26.2%), while in group β the loss was higher (31.6%). CONCLUSION: FSE significantly reduced vessel edge sharpness along the phase-encoding direction in T(1) W and PDW images. Blurring was stronger in the presence of plaque components with short T(2) times. This study shows a limitation of FSE and the potential of Multi-SE to improve the quality of carotid imaging.